PRODUCTION PROSTHETIC NOSE FOR CAD / CAM TECHNOLOGY: ADVANTAGES AND DISADVANTAGES - L.B. Yerys (Ukrainian Medical Stomatological Academy, 2015)
Traumatic defects individuals tend to remove surgically. If there are contraindications to surgery, facial defects, similar prostheses. CAD / CAM technologies are increasingly used in prosthetic dentistry, including the manufacture of artificial limbs ear, nose, orbit, upper and lower jaw. The purpose and goal of our work was to study computer technology and compared them to the production of classic maxillofacial prostheses and benefits of CAD / CAM technology in traditional prosthetic nose, for example. As an example, comparison of classical and modern production methods. Our result ektoprotezu nose and proposed methods are I.M.Oksman, S.Kosulyn. The main stages of manufacturing prosthetic nose for I.M.Oksman1. Remove the print of the face. 2. Create a prosthetic nose wax reproductions. 3. Location of functional edges. 4. Selection of color in the presence of the implant patient. 5. Gypsum wax reproductions prosthetic nose in a container.6. Replacement of wax on the plastic. 7. Connection prosthetic nose with frame glasses using pins and plastic cold polymerization. The main stages of manufacturing prosthetic nose S. Kosulin1. CT scan of the patient's face. 2. Optical scanning or pulled from the database fragments of the human person - "donor". 3. Combining electronic models plots person "donor" and the patient with the development model of the prosthesis.4. Development of the press molds for casting oil paper (wax model) prosthesis. 5. Development of programs for CNC machines for production of press - forms. 6. Production of press - forms on CNC machines. 7. Fill in the press - forms wax casting. 8. Fitting oil paper over printed in 3D - printer models face. 9. Production of rubber for oil paper form. 10. Draining silicone rubber prosthesis in shape. Comparing above listed methods of making prosthetic nose, it should be noted that the accuracy of three- dimensional model of the face is much higher than that obtained by the reflection face. After plaster creates pressure on the soft tissues of the face, the resulting model has an error that no longer provides a snug fit of the prosthesis to the skin. The use of simulation software prosthesis, creating press - forms in stalls with numerical programmed control simplifies the manufacturing process and elevates it to a new level. The inside of the nose created taking into account the presence of air channels. Printed in 3D - printer model lets face as accurately as possible using all possible retention points for placing elements denture. and use as fixing elements implants with magnetic properties. The prosthesis is attached to the special magnetic locks that make it easy to apply and remove dentures. Conclusion. The current CAD / CAM systems can produce any complexity maxillofacial prostheses, including ektoprotez nose, without the use of traditional methods. The apparent advantage of CAD / CAM systems is their high performance precision manufactured designs. Reduce the number of visits the patient through the use of and correction for fitting prosthesis made oil paper printer model on Zd face patient. The application of CAD / CAM - technology can provide the most accurate and comfortable fit prosthetic nose to the skin. Disadvantages include only the high cost of equipment and the cost of dentures. The current CAD / CAM systems can produce any complexity maxillofacial prostheses without the use of traditional methods. The apparent advantage of CAD / CAM systems is their high performance precision manufactured designs. Disadvantages include only the high cost of equipment and the cost of dentures.